2017
DOI: 10.1093/aje/kwx134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of New York City Health Policy Initiatives in Reducing Cardiovascular Disease Mortality, 1990–2011

Abstract: Beginning in 2002, New York City (NYC) implemented numerous policies and programs targeting cardiovascular disease (CVD) risk factors. Using death certificates, we analyzed trends in NYC-specific and US mortality rates from 1990 to 2011 for all causes, any CVD, atherosclerotic CVD (ACVD), coronary artery disease (CAD), and stroke. Joinpoint analyses quantified annual percent change (APC) and evaluated whether decreases in CVD mortality accelerated after 2002 in either NYC or the total US population. Our analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Moreover, implementation of community or health system policies may become more palatable if economic advantages, such as that estimated within MESA, were realized in long-term CVD costs of care. In a recent example, New York City health policy initiatives on improving healthy eating behaviors and tobacco control were associated with reductions in CVD mortality (31). The dramatic differences in cost among MESA subgroups provide insight into the substantive health care costs that could be averted by reducing the burden of risk factors (i.e., CACS) and preventing atherosclerotic disease development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, implementation of community or health system policies may become more palatable if economic advantages, such as that estimated within MESA, were realized in long-term CVD costs of care. In a recent example, New York City health policy initiatives on improving healthy eating behaviors and tobacco control were associated with reductions in CVD mortality (31). The dramatic differences in cost among MESA subgroups provide insight into the substantive health care costs that could be averted by reducing the burden of risk factors (i.e., CACS) and preventing atherosclerotic disease development.…”
Section: Discussionmentioning
confidence: 99%
“…However, once this balance is broken, the individuals may suffer from dyslipidemia, characterized by elevation of plasma LDL-C, TG and reduction of plasma HDL-C [ 7 , 8 ]. Evidence have revealed that dyslipidemia has a closely relationship with the morbidity of cardiovascular diseases (CVD) [ 9 , 10 ], which can lead to a high mortality rate in general population in both developed and developing countries all over the world [ 11 ]. Therefore, in order to reduce the risk of CVD and to develop effective therapeutic approaches against these conditions, it is important to understand the molecular metabolism underlying dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%